High-entropy oxide material and preparation method and application thereof
By designing high-entropy oxide materials, including five transition metal elements, using spinel structure and Fd-3m space group, the problems of high cost and limited performance of traditional precious metal oxide materials are solved, and efficient pseudocapacitance performance and long-life energy storage effect are achieved.
Patent Information
- Application Number
- CN202510051029.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Traditional precious metal oxide materials have limited the large-scale commercial application of supercapacitors due to their high cost and resource scarcity, and their performance has limitations, making it difficult to meet the further development of energy storage technology.
A high-entropy oxide material was designed, containing five transition metal elements (Cr, Fe, Co, Ni and Mo), with the chemical formula of (CrFeCoNiMox)3O4. The material was prepared by spinel structure and Fd-3m space group by solution synthesis and heat treatment technology.
This high entropy oxide material exhibits excellent pseudocapacitance behavior, with long charge and discharge times and high stability, suitable as supercapacitor materials and pseudocapacitor electrode materials, providing efficient energy storage solutions and economical material selection.
Smart Images

Figure CN119841623A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor materials, and in particular to a high entropy oxide material and a preparation method and application thereof. Background Art
[0002] In recent years, supercapacitors have shown broad application prospects in the field of energy storage due to their high power density, fast charging and discharging, and excellent cycle life. Among them, pseudocapacitive materials have gradually become a hot topic of research because they can store charge through reversible redox reactions, which not only significantly improves the specific capacity of supercapacitors, but also has fast kinetic characteristics and excellent stability. At present, common pseudocapacitive materials include transition metal oxides (such as RuO2, MnO2) and conductive polymers. Among them, RuO2 is considered to be one of the most promising materials due to its excellent pseudocapacitive behavior and conductive properties. However, the high cost and resource scarcity of precious metal oxides seriously limit the feasibility of their large-scale commercial application. Therefore, finding alternative materials, especially low-cost and high-efficiency alternative materials, has become one of the current research hotspots in the field of electrochemical energy storage. In this context, in order to cope with the performance limitations of traditional materials, researchers have begun to seek alternative materials with high performance and multifunctionality, which not only increase the number of active sites, but also significantly improve their electrochemical stability and charge storage capacity, laying an important foundation for the further development of energy storage technology.
[0003] In view of this, it is necessary to design an improved high entropy oxide material and its preparation method and application to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a high entropy oxide material and a preparation method and application thereof.
[0005] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a high entropy oxide material, wherein the high entropy oxide contains five transition metal elements, and the five transition metal elements are Cr, Fe, Co, Ni and Mo;
[0006] The chemical formula of the high entropy oxide is (CrFeCoNiMo x )3O4, and the range of x is 0.01-0.4, which is a spinel structure with a space group of Fd-3m.
[0007] Preferably, the value of x is 0.01:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1.
[0008] On the other hand, the present invention also provides a method for preparing the high entropy oxide material, comprising the following steps:
[0009] Dissolving nitrates corresponding to Cr, Fe, Co and Ni and ammonium paramolybdate in water to form a mixed solution, and adjusting the pH of the solution to 11 to obtain a mixed solution;
[0010] Drying the mixed solution at 70-80° C. for 10-14 hours, and grinding the product after drying to obtain a precursor powder;
[0011] The precursor powder is heated and oxidized at 700-800° C. for 1-2 hours, and then ground again after heating to obtain a high entropy oxide material.
[0012] Preferably, the molar ratio of the secondary nitrates corresponding to Cr, Fe, Co and Ni is 1:1:1:1.
[0013] Preferably, the ratio of the mass of the ammonium paramolybdate to the total mass of the five transition metal raw materials is (0.01-0.4):1.
[0014] Preferably, the ratio of the mass of the ammonium paramolybdate to the total mass of the five transition metal raw materials is 0.01:1, 0.1:1, 0.2:1, 0.3:1, or 0.4:1.
[0015] Preferably, the total concentration of solutes in the mixed solution is 0.5 mol / L.
[0016] Preferably, the pH of the solution is adjusted by using aqueous ammonia, wherein the mass percentage of the aqueous ammonia is 25-28%.
[0017] Preferably, the temperature of the heating oxidation process is increased from 30°C to 750°C, and the heating rate is 5°C / min.
[0018] In particular, the high entropy oxide material prepared by the preparation method proposed in the present invention can be used as an electrochemical supercapacitor material and a pseudocapacitor electrode material.
[0019] The beneficial effects of the present invention are:
[0020] 1. The preparation method of the high entropy oxide material provided by the present invention uses nitrates corresponding to Cr, Fe, Co, and Ni and ammonium paramolybdate as raw materials, and a high entropy oxide material with a spinel structure can be prepared by a simple solution synthesis method, and its space group is Fd-3m. Secondly, the present invention flexibly regulates the performance of the material by controlling the proportion of each metal element and the synthesis conditions, and the prepared high entropy oxide material exhibits excellent performance in the field of supercapacitors, exhibits significant pseudocapacitive behavior, has a long charge and discharge time and high stability, and provides an efficient solution and economical material selection for energy storage.
[0021] 2. The preparation method of the high entropy oxide material provided by the present invention can be realized without a specific experimental atmosphere, the reaction conditions are mild, and the experiment has high repeatability, which can realize large-scale production and is suitable for industrial applications.
[0022] 3. The method for preparing the high entropy oxide material provided by the present invention has high product purity, adjustable material properties, few by-products, and little environmental pollution, while avoiding the use of expensive or toxic reducing agents.
[0023] 4. The preparation method of the high entropy oxide material provided by the present invention increases the specific surface area of the material through the high entropy effect of multiple metal elements. The high entropy oxide can still maintain structural stability and electrochemical activity under high temperature or extreme electrochemical conditions, and is not prone to phase separation or degradation, thereby significantly improving the durability and service life of the material.
[0024] 5. The preparation method of the high entropy oxide material provided by the present invention can adjust the 3d electronic structure of the spinel structure by regulating the doping amount of Mo. The prepared high entropy oxide material exhibits high specific capacitance and excellent cycle stability, and is suitable for application in high-performance supercapacitor electrode materials, providing a new solution for the energy storage field. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an optical photograph of the high entropy oxide material prepared in Example 1 of the present invention;
[0026] Figure 2 This is the XRD pattern of the high entropy oxide material prepared in Example 1 of the present invention;
[0027] Figure 3 This is a constant current charge and discharge curve of the high entropy oxide material prepared in Example 1 of the present invention;
[0028] Figure 4 This is a constant current charge and discharge curve of the high entropy oxide material prepared in Example 2 of the present invention;
[0029] Figure 5 TEM image (100 nm) of the high entropy oxide material prepared in Example 2 of the present invention;
[0030] Figure 6 TEM image (20 nm) of the high entropy oxide material prepared in Example 3 of the present invention;
[0031] Figure 7 TEM image (10 nm) of the high entropy oxide material prepared in Example 3 of the present invention;
[0032] Figure 8 This is a constant current charge and discharge curve of the high entropy oxide material prepared in Example 3 of the present invention;
[0033] Fig. 9 This is a constant current charge and discharge curve of the high entropy oxide material prepared in Example 4 of the present invention;
[0034] Fig.10 This is a constant current charge and discharge curve of the high entropy oxide material prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0037] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0038] On the one hand, the present invention provides a high entropy oxide material, wherein the high entropy oxide contains five transition metal elements, wherein the five transition metal elements are Cr, Fe, Co, Ni and Mo, and the chemical formula of the high entropy oxide is (CrFeCoNiMo x )3O4, and the range of x is 0.01-0.4, which is a spinel structure with a space group of Fd-3m.
[0039] On the other hand, the present invention also provides a method for preparing the above-mentioned high entropy oxide material, comprising the following steps:
[0040] Dissolve the corresponding nitrates of Cr, Fe, Co and Ni and ammonium paramolybdate in water to form a mixed solution, and add ammonia water to adjust the solution pH to 11;
[0041] Drying the mixed solution at 70-80° C. for 10-14 hours, grinding the product after drying to obtain a precursor powder; wherein the total concentration of the solute in the mixed solution is 0.5 mol / L;
[0042] The oxidation precursor powder is heated at 700-800°C for 1-2 hours and then ground again to obtain a high entropy oxide material.
[0043] In some embodiments, the molar ratio of the nitrates corresponding to Cr, Fe, Co, and Ni is 1:1:1:1, and the ratio of the mass of ammonium paramolybdate to the total mass of the five transition metal raw materials is (0.01-0.4):1. Specifically, the ratio can be 0.01:1, 0.1:1, 0.2:1, 0.3:1, or 0.4:1.
[0044] In the above technical scheme, by adjusting the ratio of each metal element, heating the oxidation precursor powder at 750°C for 1 hour, an oxide material with a spinel structure is obtained. This process can utilize the high entropy effect of multiple metal elements to increase the specific surface area of the material. The obtained high entropy oxide can still maintain structural stability and electrochemical activity under high temperature or extreme electrochemical conditions, and is not prone to phase separation or degradation, thereby significantly improving the durability and service life of the material. The high entropy oxide material prepared by the above method exhibits excellent pseudocapacitive behavior in electrochemical energy storage and can be used in supercapacitors and related energy storage devices.
[0045] In some embodiments, the mass percentage of aqueous ammonia is 25-28%.
[0046] In some embodiments, the temperature of the heated oxidation process is increased from 30° C. to 750° C. at a heating rate of 5° C. / min.
[0047] Furthermore, the high entropy oxide material prepared by the preparation method proposed in the present invention can be used as an electrochemical supercapacitor material, and is particularly suitable for application in the field of pseudocapacitor electrode materials.
[0048] The high entropy oxide material and its preparation method and application proposed by the present invention are further described below in conjunction with specific embodiments:
[0049] Example 1
[0050] This embodiment prepares a high entropy oxide material, and the preparation method includes the following steps:
[0051] Weigh 1.1901g Cr(NO3)3·9H2O, 2.0204g Fe(NO3)3·9H2O, 1.4551g Co(NO3)2·6H2O, 1.4551g Ni(NO3)2·6H2O, 0.6170mg(NH4)6Mo7O 24·4H2O, and dissolved in 10mL of deionized water with a purity of 18.2MΩ·cm, first ultrasonically dissolved, and then magnetically stirred for 10min to obtain a mixed solution with a concentration of 0.5mol / L (the total concentration of the five transition metal element raw materials); slowly add ammonia water with a mass fraction of 25-28% to the mixed solution, the dropping time is 5min, until the pH of the mixed solution is 11 and remains stable, then stop dropping, and then magnetically stir at room temperature for 0.5h;
[0052] The solution was allowed to stand to allow the solid matter in the solution to settle, and then dried at 70-80° C. for 12 h. After drying, the obtained solid was ground to obtain a precursor powder;
[0053] The precursor powder is placed in a muffle furnace, and the starting temperature of the muffle furnace program is set to 30°C, the heating rate is 5°C / min, the temperature in the furnace is raised from 30°C to 750°C, and the insulation time is 1h to heat and oxidize the precursor powder; after the heating is completed, the temperature in the furnace is cooled from 750°C to 25°C at a cooling rate of 2°C / min, the product is taken out, washed with deionized water, dried at 70-80°C for 12h, and then ground again to obtain a high entropy oxide material.
[0054] The optical photograph of the high entropy oxide material prepared in this example is as follows Figure 1 As shown, the XRD pattern is Figure 2 As shown, after comparing the phase library, the results show that the diffraction peaks at 2θ of 18.9°, 30.6°, 35.9°, 37.6°, 43.6°, 54.1°, 57.5°, 63.2° and 74.7° belong to the (111), (220), (311), (222), (400), (422), (511), (440) and (533) crystal planes of the spinel structure, respectively, and no diffraction peaks of other secondary phases or impurity phases were detected, indicating that a single phase was formed.
[0055] In order to explore the performance of the high entropy oxide material prepared in the above steps as an electrochemical supercapacitor material, the test was carried out according to the following method: 5 mg of high entropy oxide material was placed in a 1.5 mL centrifuge tube, and 250 uL of deionized water, 250 mL of anhydrous ethanol, and 5 uL of a Nafion solution with a mass fraction of 5 wt% were added to the centrifuge tube in sequence. After ultrasonic vibration at 25 ° C for 30 minutes, the solution prepared in the above steps was taken with a pipette and evenly dropped on the surface of the nickel foam substrate with a length × width = 1 cm × 3 cm. After drying, it was used as a working electrode; the working electrode was activated by electrochemical activity CV, the reference electrode was a saturated calomel electrode, the counter electrode was a Pt wire, and the electrolyte was a KOH solution with a concentration of 1 mol / L. The voltage scanning range of the test process was -1.5 to 1.2 V, the scanning rate was 0.05 V / s, and the number of cycles was 200-400. The constant current charge and discharge curves of the high entropy oxide are shown in Figure 2. Figure 3 As shown in the figure, the constant current charge and discharge (GCD) curve can be seen, and the calculated surface capacitance is 84.3F / cm when tested under the condition of current density of 1A / g. 2 , which shows that this material has good energy storage performance.
[0056] Example 2
[0057] The difference between Example 2 and Example 1 is that: (NH4)6Mo7O 24 The mass of 4H2O is different from that in Example 1, specifically 6.170 mg. The other experimental parameters are the same as those in Example 1 and will not be described in detail here. The constant current charge and discharge curves of the high entropy oxide prepared in this example are shown in FIG. Figure 4 As shown in the figure, it can be seen that the charge and discharge time is increased relative to Example 1, and the calculated surface capacitance is 171.5F / cm 2 .
[0058] Example 3
[0059] The difference between Example 3 and Example 1 is that: (NH4)6Mo7O 24 The mass of 4H2O is different from that in Example 1, specifically 12.34 mg. The other experimental parameters are the same as those in Example 1 and will not be described in detail here. The TEM images of the high entropy oxide prepared in this example at different magnifications are shown in FIG. Figure 5-7 As shown in the figure, regular lattice fringes can be seen, indicating that the material has a good crystal structure; the constant current charge and discharge curve is shown in Figure 8 As shown in the figure, it can be seen that the charge and discharge time increases with the increase of Mo content, and the surface capacitance is 521.3F / cm 2 .
[0060] Example 4
[0061] The difference between Example 4 and Example 1 is that: (NH4)6Mo7O 24 The mass of 4H2O is different from that in Example 1, specifically 18.51 mg. The other experimental parameters are the same as those in Example 1 and will not be described in detail here. The constant current charge and discharge curves of the high entropy oxide prepared in this example are shown in FIG. Fig. 9 As shown in the figure, the capacitance can be calculated to be 236.7F / cm 2 .
[0062] Example 5
[0063] The difference between Example 5 and Example 1 is that: (NH4)6Mo7O 24 The mass of 4H2O is different from that in Example 1, specifically 24.68 mg. In Examples 1 to 5, (NH4)6Mo7O 24 The ratios of the mass of 4H2O to the total mass of the five transition metal raw materials are 0.01, 0.1, 0.2, 0.3 and 0.4 respectively. The other experimental parameters are the same as those in Example 1 and will not be described herein.
[0064] The high entropy oxide prepared in this example was used as a pseudocapacitor electrode material for electrochemical testing. The electrolyte was 1 mol / L KOH solution, the nickel foam covered with the high entropy oxide was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the Pt wire was used as the counter electrode. The voltage scanning range of the test process was -1.5 to 1.2 V, the scanning rate was 0.05 V / s, and the number of cycles was 200-400. The test results are as follows: Fig.10 As shown in the figure, it can be seen that at a current density of 1A / g, the surface capacitance of the sample is 205.1F / cm 2 , showing excellent pseudocapacitive performance. From the test results of Examples 1 to 5, it can be seen that the amount of Mo added has a significant effect on the pseudocapacitive performance of the high entropy oxide, because: the change in Mo content affects the number of active sites and charge storage capacity of the high entropy oxide, thereby affecting the pseudocapacitive performance.
[0065] In summary, the high entropy oxide material prepared by the present invention has a unique multi-metal composition and nanostructure, and its preparation method is simple, low-cost and highly controllable. During the preparation process, the uniform distribution of multiple metal elements is achieved through the homogeneous solution medium, and the formation of the spinel structure is optimized by heat treatment, ensuring the structural stability and high crystallinity of the material. Secondly, the high entropy oxide prepared by the preparation method proposed by the present invention effectively regulates the electronic structure by introducing the Mo element, enhances the electronic transmission performance of the material, thereby improving the specific surface area and the number of pseudocapacitor active sites, and provides an important guarantee for achieving excellent pseudocapacitor performance and charge storage capacity.
[0066] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A high entropy oxide material, characterized in that: The high entropy oxide contains five transition metal elements, which are Cr, Fe, Co, Ni and Mo; The chemical formula of the high entropy oxide is (CrFeCoNiMo x )3O4, and the range of x is 0.01-0.4, which is a spinel structure with a space group of Fd-3m.
2. The high entropy oxide material according to claim 1, characterized in that The values of x are 0.01:1, 0.1:1, 0.2:1, 0.3:1, and 0.4:
1.
3. A method for preparing the high entropy oxide material according to claim 2, characterized in that: The steps include: Dissolving nitrates corresponding to Cr, Fe, Co and Ni and ammonium paramolybdate in water to form a mixed solution, and adjusting the pH of the solution to 11 to obtain a mixed solution; Drying the mixed solution at 70-80° C. for 10-14 hours, and grinding the product after drying to obtain a precursor powder; The precursor powder is heated and oxidized at 700-800° C. for 1-2 hours, and then ground again after heating to obtain a high entropy oxide material.
4. The preparation method according to claim 3, characterized in that: The molar ratio of nitrates corresponding to Cr, Fe, Co, and Ni is 1:1:1:
1.
5. The preparation method according to claim 3, characterized in that: The ratio of the mass of the ammonium paramolybdate to the total mass of the five transition metal raw materials is (0.01-0.4):
1.
6. The preparation method according to claim 5, characterized in that: The ratio of the mass of the ammonium paramolybdate to the total mass of the five transition metal raw materials is 0.01:1, 0.1:1, 0.2:1, 0.3:1, and 0.4:
1.
7. The preparation method according to claim 3, characterized in that: The total concentration of solutes in the mixed solution is 0.5 mol / L.
8. The preparation method according to claim 3, characterized in that: The pH of the solution is adjusted by using ammonia water, and the mass percentage of the ammonia water is 25-28%.
9. The preparation method according to claim 3, characterized in that: The temperature of the heating oxidation process was increased from 30°C to 750°C at a heating rate of 5°C / min.
10. Use of the high entropy oxide material according to claim 2 or the high entropy oxide material prepared by the preparation method according to any one of claims 3 to 9 in electrochemical supercapacitor materials and pseudocapacitor electrode materials.
Citation Information
Patent Citations
High-entropy oxides for thermal barrier coating (TBC) top coats
CA3106049A1
High-entropy oxide catalytic material and preparation method thereof
CN118814211A
Cited By
Iridium-ruthenium-based high-entropy metal oxide electrocatalysts, methods of preparation, and applications
CN122879739A